1992
DOI: 10.1017/s0021932000020071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of caesarean section in Jamaica

Abstract: The prevalence and determinants of primary caesarean section in Jamaica were estimated from a survey of women aged 14-49 years. Among 2328 women reporting 2395 live hospital births during the period January 1984 to May 1989, the prevalence of caesarean section was 4 1 % . Repeat caesarean sections accounted for 1-3% of the hospital births during that period. Of the medical complications studied, prolonged labour and/or cephalopelvic disproportion carried the highest risks of primary caesarean section, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
4
11
0
Order By: Relevance
“…This was analysed by using several independent variables. Previous research suggests that women with medical complications near delivery are more likely to undergo c-section in order to improve their survival prospects as well as that of their newborns [22]. Thus, our primary independent variables included: long labour (more than 12 h), excessive bleeding around delivery, high fever/bad smelling vaginal discharge, multiple births and birth weight.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was analysed by using several independent variables. Previous research suggests that women with medical complications near delivery are more likely to undergo c-section in order to improve their survival prospects as well as that of their newborns [22]. Thus, our primary independent variables included: long labour (more than 12 h), excessive bleeding around delivery, high fever/bad smelling vaginal discharge, multiple births and birth weight.…”
Section: Methodsmentioning
confidence: 99%
“…Older mothers are more prone to undergo c-section [23,24] because of complications during pregnancy and delivery and their tendency to have bigger babies [21,22,25]. However, even in the absence of complications, studies have reported higher tendency for c-section deliveries among older, especially primiparous women [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this study suggests that the distribution of female in cesarean cases according to their age at marriage/first birth in Uttar Pradesh can be described suitably by the Type I extreme value distribution, indicating that the model age at cesarean birth is quite low, which is itself responsible for reproductive complications. Webster et al, (1992) concluded that women with obstetrics complications near delivery are more likely to undergo CD in order to improve the survival prospects of their newborns and selves. Gould et al, 1989;Signorelli et al, 1995;Cnattingius et al, 1998; suggest some maternal factors (clinical) such as long labour (≥12 hours), fetal distress, multiple births, abdominal operation, length or weight of babies and so on were considered as primary independent variables in their respective studies.…”
Section: Discussionmentioning
confidence: 99%